2022
DOI: 10.3390/en15031197
|View full text |Cite
|
Sign up to set email alerts
|

Estimating of Non-Darcy Flow Coefficient in Artificial Porous Media

Abstract: This study conducted a radial flow experiment to investigate the existence of non-Darcy flow and calculate the non-Darcy “inertia” coefficient; the experiment was performed on seven cylindrical perforated artificial porous media samples. Two hundred thirty-one runs were performed, and the pressure drop was reported. The non-Darcy coefficient β was calculated and compared with available in the literature. The results showed that the non-Darcy coefficient decreased nonlinearly and converged on a value within a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Darcy's law states that the pressure gradient is linearly proportional to the fluid velocity in porous media. However, previous research has revealed that Darcy's law is effective only within a certain range [2][3][4][5]. When the samples contain clay, their seepage behavior deviates from Darcy's law at low or high hydraulic gradients [6].…”
Section: Introductionmentioning
confidence: 93%
“…Darcy's law states that the pressure gradient is linearly proportional to the fluid velocity in porous media. However, previous research has revealed that Darcy's law is effective only within a certain range [2][3][4][5]. When the samples contain clay, their seepage behavior deviates from Darcy's law at low or high hydraulic gradients [6].…”
Section: Introductionmentioning
confidence: 93%
“…This paper used water as a working fluid, and non-Darcy's coefficient was calculated in the seven artificial samples. In a previous work, the air was used [41], and the non-Darcy flow was characterized, as well as the calculation of the non-Darcy coefficient. In general, the non-Darcy coefficient β is determined based on the following expression:…”
Section: Correlation Of Non-darcy Coefficientmentioning
confidence: 99%
“…Phipps et al [27] proposed a new method to identify the inertial coefficient in terms of the Forchheimer equation. Elsanoose et al [28] used the Radial Flow Facility (RFC) to study Non-Darcy Flow and determined the inertial coefficient. However, above studies unexceptionally discuss the flow rate characteristics under positive pressure condition.…”
Section: Introductionmentioning
confidence: 99%